Structural, Psychological and Contextual Predictors of Car Use - Semenescu, Alin; Gavreliuc, Alin (Frontiers in Psychology, 2021)
Besides its undeniable advantages, personal car use generates a wide array of problems, among which its contribution to global warming is probably the most severe. To implement sound policies that are effective in reducing private car use, it is essential to first understand its important antecedents. Structural, psychological and contextual predictors were extensively studied independently, yet integrative approaches that investigate all these factors in a single theoretical model are lacking. The present study contributes to a more comprehensive understanding of car use behavior by proposing a model that includes structural, psychological, and contextual determinants and tests this model on an international sample of drivers (N = 414). Responses were analyzed using a structural equation modeling approach. Results show that car use habits, perceived behavioral control, policy measures, fuel cost, infrastructure, temperature, and level of precipitations significantly influence car use behavior. Such results support the inclusion of both structural (i.e. hard) and psychological (i.e. soft) factors in the design of policy interventions, while also considering contextual situations. Implications for policy and practice are discussed.